Room temperature densified H3BO3 microwave dielectric ceramics with ultra-low permittivity and high quality factor for dielectric substrate applications. Issue 9 (15th June 2020) - Ding, Xianbing; Gu, Yongjun; Li, Qian; Kim, Bok-hee; Wang, Qifeng; Huang, Jinliang
Abstract: The densification and microwave dielectric properties of H3 BO3 ceramics prepared by dry pressing at room temperature were studied. The results show that pressure is the key factor of densification of H3 BO3 ceramics. No second phase appears in all the as-fabricated H3 BO3 ceramic samples. A dense H3 BO3 ceramic (relative density 97.6%) was obtained by uniaxial compression of 384 MPa for 300s and the optimal microwave dielectric properties are ε r = 2.83, Q × f = 59, 400 GHz ( f = 16 GHz), τ f = −91 ppm/°C, which make it as a prospective candidate for microwave and millimeter-wave devices such as substrates for 5G communication technology.